Historical memory in Saer's scriptural present - Guéguen, Perrine (Romanica Olomucensia, 2019)
This paper explores the link between the Argentine author Juan José Saer's narrative and historical memory. The latter usually appears in between the lines in his novels, essays, work, papers, manuscripts, and correspondence, and yet it is of great significance. The main tool of this analysis is genetic criticism, in a broad sense of the term, which gives us access to the writer's desk. This reveals a coherence in Saer's work when introducing historical motifs from Argentina's Dirty War (1976-1983) through a personal aesthetic, addressing specific portrayals of characters and temporality. Through the use of the mise en abyme of his character's dreams and memories, Saer shows the importance of the body in the aesthetic experience of horror. Moreover, he builds a series of texts connecting different episodes of the forced disappearance of two recurring characters, Elisa and Gato, across various novels, and through the character of Ángel Leto, a political activist. These gestures by Saer cause us to rethink his position when writing about political events in Argentina at the time at which they took place. Saer always claimed that he was not a politically committed writer and asserted the aesthetic independence of literature. At the same time, he embeds history into his fiction by inscribing it in the memories and recollections of his characters, which are characteristic of his writing and his negative aesthetics. Through this reading, the writer's figure shows itself as ideologically opposed to dictatorship.
Keywords: narrative; memory; genetic criticism; History; Juan José Saer; process